2008
DOI: 10.1063/1.2966339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resistance on cathodoluminescence and its application for layer sheet-resistance measurements

Abstract: The dependence of cathodoluminescence (CL) on resistances in semiconductor structures, especially on layer resistances, is described. The effect can be taken advantage of and used for characterization of sheet resistance of thin layers in semiconductor devices, as illustrated in this paper by an assessment of lateral confinements in semiconductor-laser heterostructures. At the same time, the effect, if neglected, can be detrimental for accuracy of spatially or spectrally resolved CL studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…As explained above, the impact of resistances on CL may also occur for structures without an external circuit or metallization, especially at room temperature, when forward currents of a p‐n junction diode are larger than at low temperatures. This impact should be either minimalized or considered in experiments relying on CL measurements (Czerwinski et al , 2008).…”
Section: Dependencesupporting
confidence: 56%
“…As explained above, the impact of resistances on CL may also occur for structures without an external circuit or metallization, especially at room temperature, when forward currents of a p‐n junction diode are larger than at low temperatures. This impact should be either minimalized or considered in experiments relying on CL measurements (Czerwinski et al , 2008).…”
Section: Dependencesupporting
confidence: 56%
“…with attached to contacts an external circuit of negligible resistance) the EBIC outows to the external circuit so easily that eh pairs do not recombine in InGaAs QW [4], and no EBIC spreading occurs within the structure.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in the case of specimens with a built-in strong electric eld the CL intensity may be aected by phenomena which occur even far from the excitation point [4]. The generation of electron beam induced current (EBIC) in such structures is competitive with the recombination of eh pairs, and therefore the EBIC outow causes CL quenching.…”
Section: Introductionmentioning
confidence: 99%
“…When the external circuit is open, which is typical in CL measurements, an open‐circuit voltage of the junction is generated similarly to the photovoltaic effect in a photodiode (Czerwinski et al , 2006, 2007, 2008, 2009, Rossi et al , 2008). The existing e‐h pair separation causes a forward bias between both sides of the junction.…”
Section: Methodsmentioning
confidence: 99%
“…CL studies allow also for the separation of direct material‐related degradation features of ageing (like creation of non‐radiative recombination centres), revealed by CL, from construction‐related features (like facet, contact or electron‐barrier degradation), undetected by CL. However, it has been demonstrated lately that the results of CL studies are highly dependent on the resistances existing within the measured semi‐conductor structures (Czerwinski et al , 2008, 2009). This work shows the impact of this effect on the conclusions obtained from typical studies of CL intensity degradation in InGaN‐based LDs.…”
Section: Introductionmentioning
confidence: 99%